Effect of pore-throat structure on movable fluid and gas–water seepage in tight sandstone from the southeastern Ordos Basin, China - Chang, Bin; Tong, Qiang; Cao, Cheng; Zhang, Yunde (Scientific reports, 2025)
This study investigates the micro-pore-throat structure of Upper Paleozoic tight sandstone gas reservoirs in the southeastern Ordos Basin, China, with a focus on the Yan'an gas field. The aim is to analyze the micro-pore-throat characteristics and their influence on fluid seepage to optimize gas–water two-phase flow, reservoir evaluation, and development strategies. The research integrates core analysis, thin section petrography, FE-SEM, MICP, NMR, and gas–water relative permeability tests. By combining NMR and HPMI, it offers a comprehensive characterization of pore-throat structures across various size ranges, and applies fractal dimensions to assess heterogeneity at multiple scales. Results indicate that the reservoir’s pore space is primarily composed of dissolved pores and micropores with limited connectivity and low permeability, influenced by clay content and pore-throat morphology. The pore-throat structure exhibits fractal characteristics with distinct large and small pore-throats. Larger pore-throats (> 0.1 μm) are more heterogeneous, while smaller pore-throats exhibit less variation. Permeability is largely controlled by larger pore-throats, which enhance reservoir properties. Well-developed pore-throat structures promote the occurrence of movable fluids and improve the seepage capacity of both gas and water. Larger pore-throats (> 1 μm) significantly increase relative permeability and gas displacement efficiency. A new reservoir quality parameter (H) is introduced, classifying reservoirs into four types, with Type I being most favorable for development. This parameter can be directly applied to improve reservoir management and to maximize gas recovery and optimize fluid flow. This study enhances understanding of fluid flow in tight sandstone gas reservoirs and provides a novel framework for efficient reservoir evaluation, management, and optimization in reservoir development.